The effect of mathematical modeling instruction on pre-service primary school teachers' problem solving skills and attitudes towards mathematics - Damla Koç; Aysun Nüket Elçi (Journal of Pedagogical Research, 2022)
This research was performed as a single group pretest-posttest experimental design to determine the effect of mathematical modeling instruction on pre-service primary school teachers' (PPSTs) problem-solving skills and attitudes towards mathematics. Based on an online intervention due to the pandemic, the study involved 12 PPSTs who participated through Microsoft Teams. During the first week of the six-week mathematical modeling training, data gathering tools were employed as pre-test. A four-week implementation period followed, during which mathematical modeling activities were introduced and put into practice. A post-test using data collection tools was conducted during the final week of the study. This study revealed that mathematical modeling instruction positively enhanced the problem-solving skills of PPSTs. Mathematical modeling instruction improved the skills of PPSTs in understanding the problem and carrying out plan, but did not affect their skills of devising a plan and looking back steps. PPSTs' attitudes toward mathematics were also not affected by mathematical modeling activities.